IR-UWB generate by FPGA for Non-contact Respiration Measurements - Buasombat, Panupong; Pungpa, Nonthakorn; Phasukkit, Pattarapong (My University, 2019)
Respiration rate detections and measurement has a benefit for elementary symptom in medical application. In present, most of respiration examination in medical field still needs to contact electrode with skin which is main still problem for some patient. Patients who got problem with skin like dermatitis or unable for contact case cause the problem for respiration rate detection. So, this research intends to design non-contact respiration measurement system for resolve this problem. The research applies impulse radio function with ultra-wideband wave (UWB) generate by field programmable gate array (FPGA) for detect respiration rate. In the experiment, we have designed the signal processing algorithm for respiration rate measurement by Fast-Fourier Transform (FFT) of doppler frequency from UWB detection. Result has compared respiration rate measurement between non-contact respiration rate by designed algorithm and standard contact respiration monitoring belt.
Keywords: Doppler frequency; impulse radio; respiration rate; UWB radar